2011
DOI: 10.1590/s1415-43662011000800013
|View full text |Cite
|
Sign up to set email alerts
|

Tolerância ao déficit hídrico em genótipos de feijão-caupi

Abstract: RESUMOObjetivou-se, neste trabalho, avaliar o efeito do déficit hídrico sobre as características fisiológicas e produtivas do feijão-caupi e selecionar genótipos tolerantes à seca. Avaliaram-se a condutância estomática, o potencial hídrico foliar, a temperatura das folhas e a produtividade de grãos de 20 genótipos de feijão-caupi nas condições de solo e clima de Teresina, Piauí, no ano de 2008 e se conduziram dois experimentos em delineamento de blocos ao acaso com 20 tratamentos e quatro repetições, um sob dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
26

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 20 publications
5
45
1
26
Order By: Relevance
“…Regarding the mass of 100 beans, mean values in cowpeas cultivated under full water supply were significantly higher than those in cowpeas exposed to water limiting conditions . Results from the present study confirmed that drought stress exerts a negative influence on cowpea productivity, as has been previously reported (Uarrota, 2010;Bastos et al, 2011;Nascimento et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the mass of 100 beans, mean values in cowpeas cultivated under full water supply were significantly higher than those in cowpeas exposed to water limiting conditions . Results from the present study confirmed that drought stress exerts a negative influence on cowpea productivity, as has been previously reported (Uarrota, 2010;Bastos et al, 2011;Nascimento et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Trabalhando com restrição hídrica em Vigna unguiculata (L.) Walp., Nascimento et al (2011) notaram uma elevação média de 3,5°C na temperatura média foliar quando os genótipos foram submetidos ao estresse. A diferença de temperatura foliar entre plantas submetidas ou não ao estresse fundamentase no status hídrico, no comportamento estomático e na perda de calor latente por meio da transpiração, apresentando variações quanto à tolerância em função da espécie, do ambiente, da intensidade, da duração e da hora do dia (Nogueira et al, 2001).…”
Section: Resultsunclassified
“…The parents were six cowpea genotypes within three cultivars (BRS Paraguaçu, BRS Xiquexique, and Santo Inácio) and three lines (Pingo de Ouro-1-2, CNCx698-128G, and MNC99-510F-16-1) that had previously been selected based on studies of water deficit tolerance in the cowpea Nascimento et al, 2011).…”
Section: Methodsmentioning
confidence: 99%